A Concise Review of Molecular Pathology of Breast Cancer - Gunduz, Mehmet (IntechOpen, 2015)
Cancer is one of the leading causes of death in most countries and its consequences result in huge economic, social and psychological burden. Breast cancer is the most frequently diagnosed cancer type and the leading cause of cancer death among females. In this book, we discussed gene expression and DNA abnormalities including methylation in breast cancer. A recent important topic, roles of miRNAs and their potential use in cancer therapy have been discussed in this cancer type as well. Bioinformatics is very important part of recent human genome developments and data mining and thus this topic has also been added for the readers. It is hoped that this book will contribute to development of novel diagnostic as well as therapeutic approaches, which lead to cure of breast cancer.